2017
DOI: 10.1097/ftd.0000000000000375
|View full text |Cite
|
Sign up to set email alerts
|

High Methotrexate Triglutamate Level Is an Independent Predictor of Adverse Effects in Asian Indian Rheumatoid Arthritis Patients—A Preliminary Study

Abstract: In this preliminary study, higher levels of RBC MTX-glu3 were found to be the independent predictors for adverse effects in rheumatoid arthritis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 23 publications
1
11
0
3
Order By: Relevance
“…Была установлена статистически значимая корреляция максимального уровня МТПГ 2 со снижением активности заболевания по индексу DAS28 [18], а также увеличения уровня МТПГ в эритроцитах со снижением индекса DAS28 [19]. Имеются указания, что более высокая концентрация МТПГ является предиктором развития нежелательных реакций у больных РА, но отсутствует связь между уровнем МТПГ и эффективностью препарата [20,21]. Разнородность вышеизложенных сведений можно частично объяснить разнообразием методик определения уровня метаболитов МТ.…”
Section: Discussionunclassified
“…Была установлена статистически значимая корреляция максимального уровня МТПГ 2 со снижением активности заболевания по индексу DAS28 [18], а также увеличения уровня МТПГ в эритроцитах со снижением индекса DAS28 [19]. Имеются указания, что более высокая концентрация МТПГ является предиктором развития нежелательных реакций у больных РА, но отсутствует связь между уровнем МТПГ и эффективностью препарата [20,21]. Разнородность вышеизложенных сведений можно частично объяснить разнообразием методик определения уровня метаболитов МТ.…”
Section: Discussionunclassified
“…Recently, Chen et al 19 reported the usage of an LC tandem mass spectrometry assay (LC/MS/MS) for the measurement of MTX-Glu1-5 in Caco-2 cells, showing improved selectivity and lower detection limits. In addition, according to various studies, 20 MTX-Glu was analyzed using HPLC.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Chen et al 19 reported the usage of an LC tandem mass spectrometry assay (LC/MS/MS) for the measurement of MTX‐Glu1–5 in Caco‐2 cells, showing improved selectivity and lower detection limits. In addition, according to various studies, 20 MTX‐Glu was analyzed using HPLC. Previously, Garcia‐Ac et al 21 used chromatography ionization techniques such as APPI, APCI, and ESI for the LC‐MS/MS analysis of bezafibrate, cyclophosphamide, and MTX.…”
Section: Introductionmentioning
confidence: 99%
“…A. Sandhu и соавт. [27] установили, что более высокая концентрация МТПГ3 является предиктором развития НР у больных РА, но они не установили связи между концентрацией МТПГ и ответом на терапию.…”
unclassified